Quenching of material dependence in few-cycle driven electron acceleration from nanoparticles under many-particle charge interaction. Issue 10 (17th June 2017) - Rupp, Philipp; Seiffert, Lennart; Liu, Qingcao; Süßmann, Frederik; Ahn, Byungnam; Förg, Benjamin; Schäfer, Christian G.; Gallei, Markus; Mondes, Valerie; Kessel, Alexander; Trushin, Sergei; Graf, Christina; et al.
Abstract: The excitation of nanoscale near-fields with ultrashort and intense laser pulses of well-defined waveform enables strongly spatially and temporally localized electron emission, opening up the possibility for the generation of attosecond electron pulses. Here, we investigate the electron photoemission from isolated nanoparticles of different materials in few-cycle laser fields at intensities where the Coulomb field of the ionized electrons and residual ions significantly contribute to the electron acceleration process. The dependences of the electron cut-off energy on the material's dielectric properties and electron binding energy are investigated systematically in both experiments and semi-classical simulations. We find that for sufficiently high near-field intensities the material dependence of the acceleration in the enhanced near-fields is quenched by many-particle charge-interaction.